Metabolic Modulators in Cardioprotection: A Focus on Trimetazidine - Du, Qingyou (Archives of Pharmacy, 2024)
Cardiovascular diseases remain a significant health burden worldwide, necessitating the development of effective cardioprotective strategies. Central to this pursuit is the recognition of metabolic dysregulation as a key contributor to the pathogenesis of cardiovascular diseases, particularly in the context of aging and modern lifestyle factors. Metabolic modulators, such as trimetazidine, have emerged as promising therapeutic agents by optimizing cardiac energy substrate utilization and enhancing metabolic efficiency. Trimetazidine demonstrates cardioprotective properties by inhibiting fatty acid oxidation and promoting glucose oxidation, especially under ischemic conditions where oxygen supply is limited. This metabolic shift enhances myocardial efficiency, reduces the likelihood of acidosis, and mitigates the accumulation of toxic fatty acid metabolites. Pre-clinical studies and clinical trials have demonstrated the efficacy of trimetazidine in a range of cardiac conditions, including chronic stable angina, heart failure, and diabetic cardiomyopathy, resulting in improvements in symptoms, exercise capacity, and cardiac function. Through its ability to address underlying metabolic inefficiencies, trimetazidine offers a promising adjunct therapy for patients with cardiovascular diseases, particularly those inadequately controlled by first-line treatments. This manuscript underscores the important role of metabolic modulation in the management of cardiovascular diseases and highlights trimetazidine as a valuable therapeutic option in the armamentarium against cardiac diseases.